Molecular Mechanism for the Dual Alcohol Modulation of Cys-loop Receptors - Murail, Samuel; Howard, Rebecca J.; Broemstrup, Torben; Bertaccini, Edward J.; Harris, R. Adron; Trudell, James R.; Lindahl, Erik (PLOS Computational Biology, 2012)
Author Summary Communication from one nerve cell to the next is an essential process for brain and muscle function. Nerve impulses result in release of transmitter molecules from one cell that bind to receptors on the next cell. Transmitter binding opens a pore in each receptor and ions flow across the membrane, leading to either enhancement or inhibition of new nerve impulses. These receptors are modulated by numerous drugs, including alcohols and anesthetics; identifying the precise location of modulator binding is critical for drug development. We have used computer simulation methods to model alcohol diffusion and binding to a receptor. By modifying a single residue in the receptor, we were able to move the location of the binding site and dramatically alter alcohol modulation, which supports a model with two separate binding sites for enhancement and inhibition in this family of receptors.